ANALISIS RESPON SISWA TERHADAP MEDIA CAKRAM GIZI “BUSA” PADA REMAJA SEKOLAH MENENGAH ATAS NEGERI DAN SWASTA DI KOTA YOGYAKARTA - Umi Mahmudah; Siska Puspita Sari (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
Analysis of Student Responses to "BUSA" Nutrition Disc Media in Public and Private High School Teenagers in Yogyakarta City KotaBackground: consumption of fruits and vegetables is one component of the application of balanced nutrition. Adolescents are the age group with the lowest consumption of fruits and vegetables. Lack of fruit and vegetable consumption in adolescents is associated with obesity. One of the efforts to increase fruit and vegetable consumption is nutrition education. The nutritional education process cannot be separated from the use of the media. Media cakram gizi "BUSA" is a nutrition education tool. Objective: there needs to be an analysis of student responses to the media. Objective: To determine of student responses to media cakram gizi "BUSA" in public and private high school adolescents in Yogyakarta City. Methods: this study was a cross sectional study. The research was conducted on adolescents in State Senior High School (SMAN 6 Yogyakarta, SMAN 9 Yogyakarta) and Private High School (SMA Muhammadiyah 3, SMA Muhammadiyah 4 Yogyakarta) with a total of 128 students as respondents. Media cakram gizi "BUSA" consists of 2 nutrition discs, namely “cakram gizi buah” and “cakram gizi sayur”. The research was conducted by sending media cakram gizi "BUSA" to the home address of each respondent and then the respondents filled out the response questionnaire data via google form. Student response data were analyzed and a comparison test between public and private high schools was carried out using Chi Square analysis. Results: the media “cakram gizi buah” received the same number of positive and negative responses, 32 students (50%) in public schools respectively, and received a positive response from 39 students (60.9%), 25 students (39.1%) had a negative response at school. private. While media “cakram gizi sayur” received a positive response from 34 students (53.1%), a negative response from 30 students (46.9%) in public schools and a positive response from 41 students (64.1%), a negative response from 23 students (35.9) in private schools. Conclusion: there is no difference in student responses to media cakram gizi "BUSA" in public and private senior high schools in Yogyakarta City.